PEDAGOGICAL STRATEGIES OF DEVELOPING COMMUNICАTIVЕ COMPЕTЕNCЕ IN PHILOLOGICАL ЕDUCАTION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Thе аrticlе describes the importance of developing communicative competence is crucial for students in philological education as it equips them with the linguistic, sociolinguistic, and pragmatic skills necessary for effective communication in diverse contexts. This paper explores key pedagogical strategies aimed at enhancing communicative competence among philological students. Approaches such as communicative language teaching (CLT), task-based learning (TBL), and the integration of digital technologies are highlighted as effective methods for creating interactive and authentic learning experiences. These strategies focus on fostering active participation, real-life communication scenarios, and intercultural awareness.